2020
DOI: 10.1002/sstr.202000042
|View full text |Cite
|
Sign up to set email alerts
|

Structure Design of Cathode Electrodes for Solid‐State Batteries: Challenges and Progress

Abstract: Solid‐state lithium batteries have aroused wide interest with the probability to guarantee safety and high energy density at the same time. In the past decade, fruitful endeavors have been devoted to promoting each component of these batteries, including solid electrolyte with high conductivity, dendrite‐free lithium anode, and high‐capacity cathode. However, the currently achieved cell performances are still inconsistent with the original expectations, in which interfaces severely hamper the energy output and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
44
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(46 citation statements)
references
References 164 publications
1
44
0
Order By: Relevance
“…Viewing from the charge storage mechanism and key components of ECs, this improvement requires not only excellent charge‐storage capability of the electrode materials, but also impactful strategies to optimize the design of the electrode structure. [ 4 , 5 ] Two‐dimensional (2D) nanomaterials have gradually become potential electrode materials in supercapacitor due to their built‐in electronic properties, large specific surface area, and abundant electrochemical active sites. [ 6 , 7 , 8 , 9 ] But these promising properties often come at a cost: different from the assembly of zero‐dimensional (0D) or one‐dimensional (1D) materials, 2D materials as electrodes tend to lie flat on the substrate and assemble into a compact‐stacking structure, resulting in highly tortuous ion pathways orthogonal to the current collector, which impede ion transport and cause sluggish kinetic.…”
Section: Introductionmentioning
confidence: 99%
“…Viewing from the charge storage mechanism and key components of ECs, this improvement requires not only excellent charge‐storage capability of the electrode materials, but also impactful strategies to optimize the design of the electrode structure. [ 4 , 5 ] Two‐dimensional (2D) nanomaterials have gradually become potential electrode materials in supercapacitor due to their built‐in electronic properties, large specific surface area, and abundant electrochemical active sites. [ 6 , 7 , 8 , 9 ] But these promising properties often come at a cost: different from the assembly of zero‐dimensional (0D) or one‐dimensional (1D) materials, 2D materials as electrodes tend to lie flat on the substrate and assemble into a compact‐stacking structure, resulting in highly tortuous ion pathways orthogonal to the current collector, which impede ion transport and cause sluggish kinetic.…”
Section: Introductionmentioning
confidence: 99%
“…For example, LiI incorporation in sulfides improves critical current density and compatibility of the electroltye toward Li metal [17,18]. It has also been reported that O doping enhances the interfacial stability of sulfide electrolyte toward oxide cathode material and Li metal [19][20][21][22], because O doping may suppress the side reaction between cathode and electrolyte by optimizing the space-charge layer, lowering the interfacial resistance, and mitigating the degradation of sulfide [23][24][25][26][27]. Additionally, by replacing the weak PÀS bonds with the stable PÀO bonds, O doping obviously improves the moisture stability of sulfides [28][29][30] On the other hand, Sn with good lithiophilicity is favorable for uniform Li nucleation and even lithium plating and stripping [31].…”
Section: Introductionmentioning
confidence: 99%
“…Figure S11 (Supporting Information) shows the EIS spectra of the TiO 2 -0 and TiO 2 -3 electrodes, and both EIS spectra were fitted by employing an equivalent circuit inserted in Figure S11 (Supporting Information). For the equivalent circuit, R 1 represents the ohmic resistance of the electrolyte, separator and electrode contacts, corresponding to the high frequency intercept at Z' axis; [47] R 2 represents the charge transfer resistance, corresponding to the semicircle in the high-to-medium frequency region; [48][49][50] W 2 represents the Warburg impedance correlating to Na + ion diffusion into the active material, depending on the slope of the straight line at low frequency region. [51,52] Based on the EIS results, the TiO 2 -3 electrode possesses much smaller R 2 as compared to those of the TiO 2 -0 electrode, suggesting fast charge transport for the F doped TiO 2 .…”
Section: Resultsmentioning
confidence: 99%